Pendampingan Masyarakat dalam Meningkatkan UMKM dan Pembenahan Sarana Adminisratif Rumah Dataku di Kampung Keluarga Berkualitas (KB) “Melati” Kelurahan Blotongan Kota Salatiga - Dina Anike Lumendek; Alfa Fadhila; Ode Kurniawan; Jimmy Slamet Basuki; Yosua Arya Okta Pratama; Daru Purnomo (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2021)
Kampung KB Melati Bonorejo aims to improve the quality of life of the people in the area. In the Melati Bonorejo KB village, there are UMKMs which are managed by residents. However, the existing obstacle related to UMKMs is the lack of understanding of residents about how to sell their products by utilizing existing social media. Of course, by utilizing social media, it will be easier for residents to sell their products and be able to get a bigger market. This community service activity is carried out with a workshop method that aims so that residents can find out how products are going through social media. This activity also collaborates with the owners and employees of Naruna Ceramics Salatiga who have skills in marketing, especially digital marketing.